Micelles versus Ribbons: how congeners drive the self-assembly of acidic sophorolipid biosurfactants - Dhasaiyan, Prabhu; Griel, Patrick Le; Roelants, Sophie; Redant, Emile; Bogaert, Inge N. A. Van; Prevost, Sylvain Francois; Prasad, Bhagavatula L. V.; Baccile, Niki (ChemPhysChem, 2017)
Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congeners with stearic acid (C18:0) or linoleic acid (C18:2) results in the formation of micelles that are stable over long periods of time. Conversely, the presence of only 10 to 15 % of congeners with a stearic acid chain gives fibrillar structures instead of micelles. To study the mechanisms responsible, oleic acid SLs devoid of any other congeners were prepared. Very interestingly, this sample can self-assemble into either micelles or fibers depending on minute modifications to the self-assembly conditions. The findings are supported by light scattering, small-angle X-ray scattering, transmission electron microscopy under cryogenic conditions, high-pressure liquid chromatography, and NMR spectroscopy.